Expanding Engelhardt’s Cogitation: Claim for Panorthodox Bioethics - Ladas, Ioannis (Conatus - Journal of Philosophy, 2018)
In June 2018 the Texan philosopher and distinguished bioethicist Tristram Engelhardt, Jr. crossed the great divide to meet his maker, as he would probably put it. His work remains till now the most systematic effort to fully revise Bioethics based on the doctrines of the Orthodox Christian theology, while it is also apreciseaccount ofEthics and Bioethics in the “after God” era. Engelhardt was anexcellent master of ancient Greek, medieval, western and eastern philosophy, and after heconverted from the Roman Catholic to the Eastern Orthodox Church – officially the Orthodox Catholic Church – he indulged in the works of the Holy Fathers andbecame greatly influenced by them. This is clearlymanifest in his views and continuous reference to Fathers and Ecclesiastical Writers. His conversion crucially influenced not only his bioethical views, but also his entire philosophical system. This magnificent journey obviously turned the Texan philosopher into a true Theologist – not in the academic sense, but in the one the Orthodox Catholic Church accepts, according to which “a Theologist is a person of God, from God, before God and speaks to praise God”. Engelhardt was not the first to deal with bioethical issues under the spectrum of Orthodox Theology, but he was the first to unravel both secular and Western-Church Bioethics and suggest a totally different version of Bioethicsbased on the principles of Orthodox ethics, the ceremonial and esoteric life of the Orthodox Church, having previously made himself a true communicant of both the paternal tradition and dogmatic teaching.